Social Construction Of Santri Based On Education Of Tasawuf Values In Tarbiyatul Mu'allimien Al-Islamiyah Al-Amien Prenduan Sumenep - Hadi, Saiful (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The development of information technology has a huge impact on boarding schools. Because it will provide digital information that can be accessed directly by students. For students not to be contaminated with bad information. such as the doctrine of liberalism, materialism, and hedonism, it is necessary to have an education based on Sufism values to internalize Islamic education. This is done by TMI Al-Amien Prenduan so that students have sincerity and distance themselves from the nature of liberal, material, and hedonism. For this reason, in this study, researchers used a descriptive qualitative approach with social construction theory, and this type of research used case studies. For data collection techniques through observation, interviews, and documentation. while data analysis techniques use data reduction, data presentation, and conclusion drawing. So the result of this study is the social construction of students based on Sufism value education at TMI Al-Amien Prenduan through the practice of sholawat tarekat tijaniyah, istighosah, and habituation of congregational prayer. While the supporting factor is the deliberation and assistance of the kyai and teachers to the students for 24 hours. As for the obstacles, there are violations of cottage discipline committed by the students and also due to cultural differences between the students.